A method to calculate 2nd dimension compound retention index in GC×GC system based on reference n-alkane and aromatic hydrocarbon mixture - Rizky Ilhamsyah; Daniel R. Struk; Christopher A. Heist; Peter J. Hesketh; Jean-Marie D. Dimandja (Journal of Chromatography Open, 2024)
This study presents an analytical approach for calculating retention indices of unknown compounds in the 2nd dimension of GC×GC systems by using an n-alkane-aromatic hydrocarbon (AH) reference mixture. We demonstrated that, by running a reference mixture containing a series of n-alkanes and three AH compounds in a GC×GC system, with the same run parameters as the target sample, we can mathematically obtain the retention index of unknown compounds. An analytical calculation procedure was developed and verified by using 59 test compounds. The results show that the calculated second dimension retention indices are in good agreement with those obtained from 1-D GC–MS runs, with a high coefficient of determination (R² = 0.996) and an average 2nd dimension retention index error of 14 points with standard deviation of 11.7.